Accessibility to Leisure and Culture: Evaluation of Contents by Means of Web-based Reception Studies with PRA2 - Chica-Núñez, Antonio Javier; Jiménez-Hurtado, Catalina (Journal of Audiovisual Translation, 2020)
Despite efforts undertaken by the public administration (ministries, public museums) and companies (private museums, tourist centres, streaming platforms) to bring multimodal cultural heritage closer to all citizens, the true extent of access for those with disabilities or those at risk of exclusion remains largely unknown. In recent years, Translation Studies in the field of audiovisual translation have shown a particular interest in analysing the way in which the impaired public accesses multimodal contents of all kinds. Methods (qualitative and quantitative) from other disciplines have been applied and replicated, creating a profusion of studies that seek to measure and evaluate the quality of access. This article presents the PRA2 platform, an online portal for the evaluation of accessible audiovisual resources that proposes a new way of analysing the quality of reception by developing a series of online questionnaires to target the sensory and cognitively impaired public in particular. The article presents the main features of this valuable research tool as well as the preliminary results of a study hosted by the portal regarding audio description (AD) for the Guernica painting.